2023
DOI: 10.3389/fonc.2023.1117815
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib treatment in myelofibrosis and polycythemia vera causes suboptimal humoral immune response following standard and booster vaccination with BNT162b2 mRNA COVID-19 vaccine

Abstract: Patients affected by myelofibrosis (MF) or polycythemia vera (PV) and treated with ruxolitinib are at high risk for severe coronavirus disease 2019. Now a vaccine against the virus SARS-CoV-2, which is responsible for this disease, is available. However, sensitivity to vaccines is usually lower in these patients. Moreover, fragile patients were not included in large trials investigating the efficacy of vaccines. Thus, little is known about the efficacy of this approach in this group of patients. In this prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Our findings confirmed that a third mRNA vaccine failed to warrant long-term humoral immune responses against SARS-CoV-2 in the setting of patients treated with high dose of dexamethasone or undergoing continuous MM treatment (with monoclonal antibodies alone or associated with other drugs) or reporting a low value of IgM, as reported by our working group in different hematological diseases (e.g., patients affected by myelofibrosis) ( 11 ). In fact, after two months from the third dose, most of the vaccine’s non-responder patients at two doses did not show a stable anti-SARS-CoV-2 titer, highlighting even more the increased risk of mortality in these patients related to the infection, already known from the first evidence during the beginning of the pandemic ( 12 ).…”
Section: Discussionsupporting
confidence: 88%
“…Our findings confirmed that a third mRNA vaccine failed to warrant long-term humoral immune responses against SARS-CoV-2 in the setting of patients treated with high dose of dexamethasone or undergoing continuous MM treatment (with monoclonal antibodies alone or associated with other drugs) or reporting a low value of IgM, as reported by our working group in different hematological diseases (e.g., patients affected by myelofibrosis) ( 11 ). In fact, after two months from the third dose, most of the vaccine’s non-responder patients at two doses did not show a stable anti-SARS-CoV-2 titer, highlighting even more the increased risk of mortality in these patients related to the infection, already known from the first evidence during the beginning of the pandemic ( 12 ).…”
Section: Discussionsupporting
confidence: 88%
“…Ruxolitinib inhibits the hyperactivated JAK/STAT pathway and revolutionized management of MF patients by significantly reducing the spleen size, controlling constitutional symptoms, and prolonging survival; these benefits were demonstrated in the long-term analyses of the pivotal trials COMFORT-I and COMFORT-II [ 58 , 59 , 60 ], and global real-life studies [ 61 , 62 , 63 , 64 ]. Despite being tolerated very well, ruxolitinib is immunosuppressive, can precipitate opportunistic infections, alter cytokine responses [ 65 , 66 , 67 ], and may impair response to normal immune stimulation (e.g., SARS-CoV-2 vaccinations) [ 68 , 69 ]. Anemia is the most frequent reason leading to dose reduction/interruption of ruxolitinib in MF patients [ 70 ].…”
Section: Concurrent Acvr1 and Jak Inhibition In Myelofibrosismentioning
confidence: 99%
“…Malignancies (especially hematological), immunodeficiency states, and recent use of B‐cell–depleting therapies are well‐described clinical conditions capable of preventing an adequate vaccine response 3,4 . Several studies based on different hematological diseases were conducted to evaluate the ability of these patients to develop a protective level of antibody response, including by our group 5–7 …”
Section: Introductionmentioning
confidence: 99%
“…3,4 Several studies based on different hematological diseases were conducted to evaluate the ability of these patients to develop a protective level of antibody response, including by our group. [5][6][7] Furthermore, significant infection-related mortality besides receiving the vaccine in these subgroups of patients has been reported. On the other hand, the available new therapeutic strategies (e.g., monoclonal antibodies, antivirals) can limit the risk of worse outcomes.…”
Section: Introductionmentioning
confidence: 99%